O problema da legitimidade e a limitação do poder régio na Hispania visigoda: o reinado de Ervígio (680-687) - Frighetto, Renan (Gerión. Revista de Historia Antigua, 2005)
The confrontation between royal and nobiliarchic institutions throughout. Ancient times was constant, leading to a fragmentation of the monarch's centralizing authority. In Visigothic Hispania of the seventh century this confrontation provoke the king's weaken, specially during Ervigius reign.